Optimization of Care Pathways Through Technological, Clinical, Organizational and Social Innovations: A Qualitative Study - Jean-Baptiste Gartner; André Côté (SAGE Publishing, 2023)
Numerous calls at national and international level are leading some countries to seek to redesign the provision of healthcare and services. Care pathways have the potential to improve outcomes by providing a mechanism to coordinate care and reduce fragmentation and ultimately costs. However, their implementation still shows variable results, resulting in them being considered as complex interventions in complex systems. By mobilizing an emerging approach combining action research and grounded theory methodology, we conducted a pilot project on care pathways. We used a strongly inductive process, to mobilize comparison and continuous theoretical sampling to produce theories. Forty-two interviews were conducted, and participant observations were made throughout the project, including 60 participant observations at meetings, workshops and field observations. The investigators kept logbooks and recorded field notes. Thematic analysis was used with an inductive approach. The present model explains the factors that positively or negatively influence the implementation of innovations in care pathways. The model represents interactions between facilitating factors, favourable conditions for the emergence of innovation adoption, implementation process enablers and challenges or barriers including those related specifically to the local context. What seems to be totally new is the embodiment of the mobilizing shared objective of active patient-partner participation in decision-making, data collection and analysis and solution building. This allows, in our opinion, to transcend professional perspectives for the benefit of patient-oriented results. Finally, the pilot project has created expectations in terms of spread and scaling. Future research on care pathway implementation should go further in the evaluation of the multifactorial impacts and develop a methodological framework of care pathway implementation, as the only existing proposition seems limited. Furthermore, from a social science perspective, it would be interesting to analyse the modes of social valuation of the different actors to understand what allows the transformation of collective action.